Regulatory T cell niche in the bone marrow, a new player in Haematopoietic stem cell transplantation. (May 2023) - Ashman, Jed; Mutsonziwa, Nyasha; Romano, Marco; Kordasti, Shahram; Lombardi, Giovanna; Shangaris, Panicos
Abstract: Challenges in haematopoietic stem cell transplantation such as low bone marrow (BM) engraftment, graft versus host disease (GvHD) and the need for long-term immunosuppression could be addressed using T regulatory cells (Tregs) resident in the tissue of interest, in this case, BM Tregs. Controlling the adverse immune response in haematopoietic stem cell transplantation (HSCT) and minimising the associated risks such as infection and secondary cancers due to long-term immunosuppression is a crucial aspect of clinical practice in this field. While systemic immunosuppressive therapy could achieve reasonable GvHD control in most patients, related side effects remain the main limiting factor. Developing more targeted immunosuppressive strategies is an unmet clinical need and is the focus of several ongoing research projects. Tregs are a non-redundant sub-population of CD4 + T cells essential for controlling the immune homeostasis. Tregs are known to be reduced in number and function in autoimmune conditions. There is considerable interest in these cells as cell therapy products since they can be expanded in vitro and infused into patients. These trials have found Treg therapy to be safe, well-tolerated, and with some early signs of efficacy. However, Tregs are a heterogeneous subpopulation of T cells, and several novel subpopulations have been identified in recent years beyond the conventional thymic (tTregs) and peripheral (pTregs). There is increasing evidence for the presence of resident and tissue-specific Tregs. Bone marrow (BM) Tregs are one example of tissue-resident Tregs. BM Tregs are enriched within the marrow, serving a dual function of immunosuppression and maintenance of haematopoietic stem cells (HSCs). HSCs maintenance is achieved through direct suppression of HSCs differentiation, maintaining a proliferating pool of HSCs, and promoting the development of functional stromal cells that support HSCs. In this review, we will touch upon the biology of Tregs, focusing on their development and heterogeneity. We will focus on the BM Tregs from their biology to their therapeutic potential, focusing on their use in HSCT.